The The Development of a Demonstration Video for the Topic of Fruit Carving in the Food Presentation Arts Course - Rahmat, Hilmi Nazri; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2023)
The demonstration video for the topic of fruit carving in the food presentation art course is a self-directed learning material for users in the field of hospitality. Self-directed learning in practical learning by focusing on this video increases motivation, understanding, and clarity in learning. The purpose of this study is to design and develop a demonstration video for the topic of fruit carving. The study is also carried out to identify the functionality of the product and test the level of usability of the product against the readiness of self-directed learning. This study uses quantitative research in product development by applying the ADDIE development model for product development and the Garrison learning model in the development of learning content. The researchers used a purposive sampling method of 30 students in the field of catering by choosing two experts in the field of instructional design and two experts in the field of catering for a validation process. Data was collected and analyzed using frequency and percentage values based on a checklist form that had been distributed. Each item is classified into a group and frequency data is recorded as a percentage. The study’s findings show that experts agree 100% on the elements of content, functionality, and usability of the product. While in the effectiveness of the product, 94% agree with self-management, 96.7% agree on self-monitoring and 93.76% agree on motivational elements through the Garrison model. The research proposal is to expand on various learning topics, especially in the practical field of self-directed learning.